Rancang Bangun Kerangka Tanaman Hidroponik Politeknik Negeri Batam - Pamungkas, Nurman; Widiastuti, Hanifah; Restu, Fedia; Leksonowati, Nur Fitria Pujo; Arifin, Nurul Laili; Muvariz, Mufti Fathonah; Ulfah, Nurul; Widodo, Widodo; Baharudin, Budi; Fajrin, Aulia; Fyona, Annisa; Kamsyah, Domi; Gemala, Mega; Rosbandrio, Wowo; Aryswan, Adhe; Siregar, James; Saputra, Hendra; Irawan, Benny Haddli; Saputra, Ihsan; Ariyanto, Nugroho Pratomo; Mutiarani, Mutiarani (Politeknik Negeri Batam, 2023)
The hydroponic pilot project in the Batam State Polytechnic area was motivated by problems with economic conditions and declining health conditions during the Covid-19 pandemic. This project is expected to support the